Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1120/jacmp.v11i2.3183
|View full text |Cite
|
Sign up to set email alerts
|

An organ and effective dose study of XVI and OBI cone‐beam CT systems

Abstract: The main purpose of this work was to quantify patient organ doses from the two kilovoltage cone beam computed tomography (CBCT) systems currently available on medical linear accelerators, namely the X‐ray Volumetric Imager (XVI, Elekta Oncology Systems) and the On‐Board Imager (OBI, Varian Medical Systems). Organ dose measurements were performed using a fiber‐optic coupled (FOC) dosimetry system along with an adult male anthropomorphic phantom for three different clinically relevant scan sites: head, chest, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 24 publications
7
52
0
Order By: Relevance
“…Several studies reported on the effective doses from kilovoltage CBCT [6,31,33,34,39,43,90]. In all these cases, the absorbed dose was measured in an anthropomorphic phantom and converted to effective dose using the tissue weighting factors obtained from International Commission on Radiological Protection (ICRP) reports 60 and 103 [91,92].…”
Section: Estimation Of Effective Dose From Cbct Imagingmentioning
confidence: 99%
“…Several studies reported on the effective doses from kilovoltage CBCT [6,31,33,34,39,43,90]. In all these cases, the absorbed dose was measured in an anthropomorphic phantom and converted to effective dose using the tissue weighting factors obtained from International Commission on Radiological Protection (ICRP) reports 60 and 103 [91,92].…”
Section: Estimation Of Effective Dose From Cbct Imagingmentioning
confidence: 99%
“…This was measured by Hyer et al . using a fiber-optic coupled dosimetric system (Hyer et al , 2010). The scan parameters were as follows: 125 kV, 800 ms, 13 mA and 655 projections.…”
Section: Discussionmentioning
confidence: 99%
“…Hyer et al . (Hyer et al , 2010) estimated effective dose to the pelvis, but did not study the dose dependence on projection angle. Furthermore, their field size was that of a conventional pelvic CBCT scan, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Daily online imaging has the best potential to correct for target position variation through the course of treatment. However, a concomitant pelvic dose of 3.7-4.3 mSv per CBCT exposure 14 should be taken into consideration when daily imaging is used. Further research is required to determine the optimal schedule for CBCT verification.…”
Section: Discussionmentioning
confidence: 99%